Interplay of structural dynamics and electronic effects in an engineered assembly of pentacene in a metal–organic framework. Issue 12 (12th February 2021) - Haldar, Ritesh; Kozlowska, Mariana; Ganschow, Michael; Ghosh, Samrat; Jakoby, Marius; Chen, Hongye; Ghalami, Farhad; Xie, Weiwei; Heidrich, Shahriar; Tsutsui, Yusuke; Freudenberg, Jan; Seki, Shu; et al.
Abstract : Pentacene assembled into 1D arrays using a metal–organic framework (MOF) approach. This cofacial packing motif, which is not present in pentacene bulk, shows an interesting interplay of band-like and hopping-type transport. Abstract : Charge carrier mobility is an important figure of merit to evaluate organic semiconductor (OSC) materials. In aggregated OSCs, this quantity is determined by inter-chromophoric electronic and vibrational coupling. These key parameters sensitively depend on structural properties, including the density of defects. We have employed a new type of crystalline assembly strategy to engineer the arrangement of the OSC pentacene in a structure not realized as crystals to date. Our approach is based on metal–organic frameworks (MOFs), in which suitably substituted pentacenes act as ditopic linkers and assemble into highly ordered π-stacks with long-range order. Layer-by-layer fabrication of the MOF yields arrays of electronically coupled pentacene chains, running parallel to the substrate surface. Detailed photophysical studies reveal strong, anisotropic inter-pentacene electronic coupling, leading to efficient charge delocalization. Despite a high degree of structural order and pronounced dispersion of the 1D-bands for the static arrangement, our experimental results demonstrate hopping-like charge transport with an activation energy of 64 meV dominating the band transport over a wide range of temperatures. A thorough combined quantum mechanical and molecular dynamics investigation identifies frustrated localized rotations of the pentacene cores as the reason for the breakdown of band transport and paves the way for a crystal engineering strategy of molecular OSCs that independently varies the arrangement of the molecular cores and their vibrational degrees of freedom.